Research Progress on the Extractive Metallurgy of Titanium and Its Alloys. (17th November 2021) - Song, Yulai; Dou, Zhihe; Zhang, Ting-an; Liu, Yan
ABSTRACT: Titanium ores are plentiful in the earth crust, and the corresponding metal content ranks as the fourth among structural metals; the application of titanium metal is restricted for its high cost in spite of its excellent mechanical properties, corrosion, and oxidation resistance. Titanium metal was first produced with Hunter process yet this has been practically replaced by Kroll process which contains carbochlorination of rutile and ilmenite to obtain TiCl4, followed by metallothermic reduction with magnesium. The complex procedure, huge investment, and considerable energy consumption have markedly prevented the development of titanium. Electrolysis has been proposed by Fray et al. in the early twenty-first century, developed and derived by many other researchers, involving both anodic and cathodic process, use TiCl4 and titania as raw materials. However, the efficiency and continuity issues remain inevitable, while self-propagating high-temperature synthesis (SHS) seems a good alternative for its rapid, continuous, and controllable characteristics. The extractive metallurgy of titanium and its alloy plays an important role in the effective utilization of titanium. At present, there is a lack of the latest review on the extractive metallurgy technology of titanium and its alloys. In this paper, the development status of extractive metallurgy of titanium and its alloys are reviewed, and finally, the direction of extractive metallurgy of titanium and its alloys is prospected.